2016
DOI: 10.1111/micc.12320
|View full text |Cite
|
Sign up to set email alerts
|

Retinal microcirculation in association with caffeinated and alcoholic drinks in subjects at increased cardiovascular risk

Abstract: Alcohol and alcoholic drinks' consumption were not associated, while decaffeinated coffee and caffeine consumption were associated in an opposing pattern with retinal vessel calibers. The reason of this controversy merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In individuals with, versus without, a history of the cardiovascular disease, the minimum of the J-curve in the association of total alcohol consumption with the total MVD composite score was located at higher levels of total alcohol consumption, possibly because levels of background oxidative stress are higher in individuals with, versus without, a history of cardiovascular disease [ 5 , 74 ]. Biologically, higher levels of ethanol-induced oxidative stress may be required to induce more oxidative stress than already present in the background [ 5 , 27 ]. Indeed, consistent with this concept, we found that the minimum in the J-curve was located at higher levels of alcohol consumption in individuals with, versus without, a cardiovascular risk factor (for any individual risk factor under study).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In individuals with, versus without, a history of the cardiovascular disease, the minimum of the J-curve in the association of total alcohol consumption with the total MVD composite score was located at higher levels of total alcohol consumption, possibly because levels of background oxidative stress are higher in individuals with, versus without, a history of cardiovascular disease [ 5 , 74 ]. Biologically, higher levels of ethanol-induced oxidative stress may be required to induce more oxidative stress than already present in the background [ 5 , 27 ]. Indeed, consistent with this concept, we found that the minimum in the J-curve was located at higher levels of alcohol consumption in individuals with, versus without, a cardiovascular risk factor (for any individual risk factor under study).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is some evidence that alcohol consumption may be a determinant of MVD, and that the association of alcohol consumption with MVD may be J-shaped, however, this evidence has important limitations [ 15 53 ]. First, many population-based studies did not quantify the amount of alcohol consumption [ 15 , 18 , 21 , 27 , 28 , 32 , 33 , 37 , 40 , 44 , 47 , 50 , 52 ]; did not take potential cardiovascular [ 16 20 , 22 , 25 , 26 , 29 , 34 , 35 , 38 , 39 , 41 , 45 , 46 , 48 , 49 , 51 , 53 ] and/or lifestyle [ 23 , 24 , 31 , 32 , 42 , 43 ] confounders in to account; and/or did not account for sick quitters [ 19 , 22 , 30 , 34 , 36 , 42 , 43 ] (i.e. individuals who quit drinking and are thought to have an increased cardiovascular risk) [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it caused a measurable change in retinal capillary perfusion, retinachoroid blood flow, and CBF in healthy participants. Compared to younger and healthier people, caffeine may elevate BP and constrict retinal vessels more effectively in older individuals and those with hypertension, diabetes, Table 3 Cerebral blood flow and retina-choroid blood flow parameters (mL/100 mL/min) before and after drinking coffee (n = 4) or water (n = 4) or retinal microvascular disorders [36,37]. Therefore, it reminds us the possible health risks after drinking a moderate dosage of coffee.…”
Section: Discussionmentioning
confidence: 99%
“…A posteriori DPs are based on statistical methods and can incorporate actual characteristics of individuals' choices in relation to the development of a disease (18) and they provide new insight on the relationship between diet and disease. Limited data are available on the association between a posteriori defined DPs and the early dysfunction of the microcirculation which is a common pathophysiological mechanism in the development of insulin resistance, CVD and type 2 diabetes mellitus (19,20) .…”
mentioning
confidence: 99%